To solve the equation \(2x(4x+1)=11\) using the quadratic formula, we first need to rearrange the equation into standard form.
-
Expand the left side: \[ 8x^2 + 2x = 11 \]
-
Rearrange it to set it to 0: \[ 8x^2 + 2x - 11 = 0 \]
Now we identify the coefficients \(a\), \(b\), and \(c\) in the standard form \(ax^2 + bx + c = 0\):
- \(a = 8\)
- \(b = 2\)
- \(c = -11\)
Next, we apply the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Substituting the values of \(a\), \(b\), and \(c\) into the formula:
-
Calculate the discriminant: \[ b^2 - 4ac = 2^2 - 4 \cdot 8 \cdot (-11) = 4 + 352 = 356 \]
-
Now plug the values into the quadratic formula: \[ x = \frac{-2 \pm \sqrt{356}}{2 \cdot 8} \]
-
Simplify: \[ x = \frac{-2 \pm \sqrt{356}}{16} \]
Next, simplify \(\sqrt{356}\). Since \(356 = 4 \cdot 89\), we have: \[ \sqrt{356} = \sqrt{4} \cdot \sqrt{89} = 2\sqrt{89} \]
So we substitute back: \[ x = \frac{-2 \pm 2\sqrt{89}}{16} \]
Factor out the 2 in the numerator: \[ x = \frac{2(-1 \pm \sqrt{89})}{16} \] \[ x = \frac{-1 \pm \sqrt{89}}{8} \]
Thus, the solutions are: \[ x = \frac{-1 + \sqrt{89}}{8}, \quad x = \frac{-1 - \sqrt{89}}{8} \]
Finally, the full answer is:
- \(x = \frac{-1 + \sqrt{89}}{8}, \frac{-1 - \sqrt{89}}{8}\)